2022
DOI: 10.1039/d2ra01789j
|View full text |Cite
|
Sign up to set email alerts
|

A novel, highly sensitive electrochemical 1,4-dioxane sensor based on reduced graphene oxide–curcumin nanocomposite

Abstract: Reduced graphene oxide–curcumin (rGO–CM) nanocomposite was prepared from graphite oxide using curcumin. The rGO–CM/GCE was used for highly sensitive 1,4-dioxane detection. The LOD obtained (0.13 μM) was lower than the WHO guideline value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These peaks are suppressed and shifted in the spectra of the solution with both AgCNT and 25OHD, confirming a strong interaction between them. 34 Analytical parameters.-Reliability and stability.-Reliability and stability of the response are critical parameters to validate a sensor. The reliability of the response was assessed by comparing the ΔR values obtained consecutively (5 runs) in 100 nM 25OHD solution using AgCNT/GCE.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are suppressed and shifted in the spectra of the solution with both AgCNT and 25OHD, confirming a strong interaction between them. 34 Analytical parameters.-Reliability and stability.-Reliability and stability of the response are critical parameters to validate a sensor. The reliability of the response was assessed by comparing the ΔR values obtained consecutively (5 runs) in 100 nM 25OHD solution using AgCNT/GCE.…”
Section: Resultsmentioning
confidence: 99%
“…Sana et al 2022 developed a reduced graphene oxide-curcumin (rGO-CM) nanocomposite sensor for the electrochemical sensing of 1,4-dioxane. The rGO-CM sensor showed high sensitivity of 19.36 mA mM −1 cm −2 in the linear range 0.1 to 100 mM with 0.13 mM limit of detection (LOD) [34]. Iffath et al, 2023 reported the fabrication of a curcumin quantum dots (CMQD)-based electrochemical sensor for the ultrasensitive detection of dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, curcumin was conjugated with GO and loaded into liposomes, which may improve the preformulation characteristics. , By combining both of them, they may show a synergistic response as antimicrobial. Liposomes have received a lot of interest in the topical drug delivery system because of their amphiphilic character, which makes them a superior penetration enhancer for the cutaneous route of administration than traditional formulations. Therefore, the objectives of this work were to achieve better antimicrobial actions over the CUR-loaded liposomes. As a result, the primary goal of this work was complex (CUR + GO complex) development, and its characterization was investigated.…”
Section: Introductionmentioning
confidence: 99%